2003
DOI: 10.1128/iai.71.4.1774-1783.2003
|View full text |Cite
|
Sign up to set email alerts
|

Afa/Dr Diffusely AdheringEscherichia coliInfection in T84 Cell Monolayers Induces Increased Neutrophil Transepithelial Migration, Which in Turn Promotes Cytokine-Dependent Upregulation of Decay-Accelerating Factor (CD55), the Receptor for Afa/Dr Adhesins

Abstract: Ulcerative colitis and Crohn's disease are inflammatory bowel diseases thought to involve strains of Escherichia coli. We report here that two wild-type Afa/Dr diffusely adhering E. coli (DAEC) strains, C1845 and IH11128, which harbor the fimbrial F1845 adhesin and the Dr hemagglutinin, respectively, and the E. coli laboratory strain HB101, transformed with the pSSS1 plasmid to produce Afa/Dr F1845 adhesin, all induced interleukin-8 (IL-8) production and transepithelial migration of polymorphonuclear leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 74 publications
1
60
0
Order By: Relevance
“…Bétis et al reported that the DAEC strains C1845 and IH11128 also triggered a proinflammatory signal in intestinal epithelial cells (3,4). In the present study we attempted to determine whether all afa-positive DAEC strains isolated from diarrheal stools could induce IL-8 secretion in cultured human epithelial cells to the same extent as EAggEC organisms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bétis et al reported that the DAEC strains C1845 and IH11128 also triggered a proinflammatory signal in intestinal epithelial cells (3,4). In the present study we attempted to determine whether all afa-positive DAEC strains isolated from diarrheal stools could induce IL-8 secretion in cultured human epithelial cells to the same extent as EAggEC organisms.…”
Section: Discussionmentioning
confidence: 94%
“…French groups have continued to investigate these Afa-positive DAEC and have provided information regarding their molecular bacteriology (2,(14)(15)(16)(31)(32)(33)(34). Furthermore, Bétis et al (3,4) found that two DAEC strains induced interleukin-8 (IL-8) in human colonic epithelial cell line, T84.…”
mentioning
confidence: 99%
“…F1845-induced transepithelial migration of PMNLs triggers the synthesis of TNF-␣ and IL-1␤, which in turn promotes the upregulation of brush border-associated hDAF, increasing the adhesion of Afa/Dr DAF/CEACAMs DAEC to the brush border, and abnormal expression of hDAF at the basolateral domain of the fully differentiated T84 cells (808). PMNLs that have transmigrated across fully differentiated T84 monolayers show an elevated global caspase activity, indicative of apoptosis, and a reduced capacity to phagocytose Afa/Dr DAF/CEACAMs DAEC (809).…”
Section: Host Cellular Defense Responsesmentioning
confidence: 99%
“…This stimulates the enterocytes to synthesize TNFa and IL-1β and upregulate DAF to strengthen bacterial adhesion. 75 DAEC can interact with the transmigrating PMNs and induce type I pili-dependent IL-8 release. 76 Transmigrated PMNs are also induced to undergo apoptosis after interaction with DAEC and have a diminished phagocytic capacity, prolonging bacterial persistence in the gut.…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%